Implementasi Guru PJOK dalam Penanaman Karakter Peduli Lingkungan pada Siswa SDN 2 Cakranegara - Karisman Karisman; Maulidin Maulidin; Muhsan Muhsan (Jurnal Porkes, 2026)
This study was motivated by the low level of environmental awareness among students at SDN 2 Cakranegara, such as littering and failing to put away sports equipment properly. The study aims to describe how Physical Education (PJOK) teachers implement character education to instill environmental awareness, as well as to identify supporting factors, barriers, and types of activities. The research method is qualitative, specifically a case study. The research subjects were two PJOK teachers selected through purposive sampling based on the criterion of having at least five years of experience. Data collection techniques included interviews, observations, and documentation. Data analysis utilized the Miles and Huberman model, with data validity tested through member checking and triangulation. The results showed that implementation occurred in three stages: planning the integration of character values into lesson plans, implementing role-modeling and habit-forming strategies, and evaluating student behavior. Supporting factors included support from the principal and available facilities. Barriers included a lack of student awareness and time constraints. Activities included cleaning the field, maintaining equipment, and planting greenery. The conclusion of this study is that physical education teachers play a strategic role as role models, facilitators, motivators, and mentors in instilling a character of environmental care.